ELECTRONIC DOCUMENT MANAGEMENT SYSTEM AS A TOOL FOR OPERATIONAL MANAGEMENT ON CONSTRUCTION SITE - A. Saitgaraev (Вестник университета)
The article analyzes the composition of the executive documentation, which works foreman, and identifies the benefits of implementing electronic document management system at the construction site.